Convenções e os acordos coletivos: estudo das cláusulas de proteção e de promoção da saúde dos jornalistas profissionais de Belo Horizonte e Região Metropolitana, no período de 2010 a 2018. - NÁZIA APARECIDA PEREIRA (2018)
Excessive work day, low salary, professionals without enough time to take care of themselves: all of this, along with harassment of bosses, is in the determination bases of the processes about illness and professional journalists. The understanding is that the ethic while making journalism is still an embryonic process and request the acceleration of new mechanisms to have a stronger relationship: journalistic, news, communication vehicle and public. We can observe a little involvement coming from the professionals who choose the silent, instead of fighting for your own defense. Researches about this reality are scarce. The focus of the inquiry: to study clauses which address the protection and promotion of the health of professional journalists in Belo Horizonte and Metropolitan area, which were chosen in Convention and Collective Agreements, with emphases in the clause called Code of Ethics, between 2010 and 2018. It was made a qualitative study, using the method of documentary analysis and it was studied clauses of the Convention and Collective Agreements, which is related to the health of journalists, between 2010 and 2018. Careful and thorough reading the existent clauses in the mentioned documents, it was selected eighteen between them, regarding the health of journalists, including the Code of Ethics. The analyses were made starting from two methodologic procedures: first of all, the comparative horizontal reading, meaning a reading considering each selected clause within the time. Then, the comparative reading with the actual labor legislation during that time. Also it is part of this study the reading of meeting minutes of the Ethics Committee and Freedom of the Press from SJPMG, between 2002 and 2006, whose data were discussed at the Freedom of the Press World Ranking of 2018: The Hate Towards Journalism is a Threat to Democracy, disclosed by the Non-Governmental Organization Reporters Without Borders (ONG RSF). It was verified that the clauses and their respective contents are being repeated year by year and, in most of the situations, reaffirms what was addressed in the labor legislation or in the social security rules. It was not observed advances toward the promotion of healthy work environments, but, instead, some of the differentiated achievements, when making comparison between the Conventions and the Agreement of Radio and Television and newspaper and magazines. About violence against journalists, the research showed that Brazil is pointed as one of the most dangerous country in South American to practice journalism. Also, collective politics to take care of the professional journalist health is not mentioned, especially those who act in camp. Thus, it is pointed out the necessity of dialogue between the syndicate of the category and works, with the goal of building collective strategies that can contribute to give a lurch in the work environment and in the quality of life for the journalists. It is necessary the edition of new laws that prevent journalism with ethics and penalize the irresponsible media. Key words: work health. Journalists. Ethics. Syndicate.